1995
DOI: 10.1146/annurev.iy.13.040195.002101
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Through the Hematopoietic Cytokine Receptors

Abstract: Hematopoiesis is regulated through the interaction of a variety of growth factors with specific receptors of the cytokine receptor superfamily. Although lacking catalytic domains, all the receptors couple ligand binding to the rapid induction of protein tyrosine phosphorylation. This is mediated through a novel family of protein tyrosine kinases termed the Janus kinases (Jaks) which associate with the receptors and are activated following ligand binding. Depending upon the cytokine/receptor system, one or more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
309
0
6

Year Published

1997
1997
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 587 publications
(317 citation statements)
references
References 43 publications
2
309
0
6
Order By: Relevance
“…All of the signaling proteins known to be activated by the EpoR, including JAK2, STAT5, SH-PTP1, Grb2, and Ras, are also activated by other cytokine receptors (6,7). Here we show that the unique outcome of EpoR signaling is not due to any unique signals it may generate, but instead is encoded in the cellular environment of erythroid progenitors.…”
Section: Wild-type Prlr Can Fully Support Differentiation Of Erythroimentioning
confidence: 67%
“…All of the signaling proteins known to be activated by the EpoR, including JAK2, STAT5, SH-PTP1, Grb2, and Ras, are also activated by other cytokine receptors (6,7). Here we show that the unique outcome of EpoR signaling is not due to any unique signals it may generate, but instead is encoded in the cellular environment of erythroid progenitors.…”
Section: Wild-type Prlr Can Fully Support Differentiation Of Erythroimentioning
confidence: 67%
“…Autophosphorylation of receptor tyrosine kinases creates docking sites to which cytoplasmic signaling proteins bind either directly (Kazlauskas et al, 1989) or via adapter molecules such as Grb2 (Downward, 1994). Signaling through receptors without intrinsic enzymatic activity relies on the activity of constitutively and/or inducibly bound kinases (Ihle et al, 1995;Chan et al, 1994;Cambier et al, 1994). Some nonreceptor tyrosine kinases (NRTKs) also communicate with the plasma membrane and elicit their function independent of cell surface receptors (Resh, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…for the TGFa and SCF receptors and members of the Jak family (Hayman et al, 1993;Beug et al, 1995;Ihle et al, 1995;Steinlein et al, 1995;Broudy, 1997;Wessely et al, 1997). By using a PCRbased strategy and targeting the conserved kinase encoding region we have attempted (i) to monitor tyrosine kinase gene expression in erythroid cells when cells di erentiate and (ii) to isolate and identify tyrosine kinases that have so far not been implicated in erythroid cell development, and also (iii) to discover new members of the tyrosine kinase family with a potential function in erythroid cells.…”
Section: Discussionmentioning
confidence: 99%
“…c-kit, IGFR and Jak1 expression was e ectively downregulated in both di erentiating SCF and TGFa progenitors, albeit with di erent kinetics. Jak1 is of particular interest since Jak proteins provide a link between cytokine receptors without intrinsic tyrosine kinase activity and protein substrates, such as the STAT transcription factors, that are tyrosine phosphorylated upon receptor activation and induce speci®c changes in gene expression (Ihle et al, 1995). Interestingly, it has been reported that EGFR and c-kit activate STAT factors in hematopoietic cells (Mellitzer et al, 1996;DeBerry et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation